Platinum‐Catalysed Ring‐Opening Isomerisation of Piperidine Cyclopropanes. Issue 4 (9th March 2018) - Barát, Viktor; Kasinathan, Sivarajan; Bates, Roderick W.
Abstract: A range of cyclopropyl‐fused N ‐tosyl piperidines have been synthesised and shown to undergo ring‐opening isomerisation on treatment with platinum(II) catalysts. The products can have either an endo ‐cyclic or exo ‐cyclic double bond. The selectivity is influenced by reaction temperature, solvent and, most significantly, the catalyst. A mechanism involving C−C bond activation and β‐hydride elimination is proposed. When β‐hydride elimination is blocked, a stereospecific platinum‐driven Wagner–Meerwein shift is observed. Abstract : Pt open that ring ! A range of cyclopropyl‐fused N ‐tosyl piperidines have been synthesised and shown to undergo ring‐opening isomerisation on treatment with platinum(II) catalysts. The products can have either an endo ‐cyclic or exo ‐cyclic double bond. The selectivity is influenced by reaction temperature, solvent and, most significantly, the catalyst.